2006
DOI: 10.1074/jbc.m513525200
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of Active Mammalian Respiratory Chain Supercomplexes

Abstract: In the inner mitochondrial membrane, the respiratory chain complexes generate an electrochemical proton gradient, which is utilized to synthesize most of the cellular ATP. According to an increasing number of biochemical studies, these complexes are assembled into supercomplexes. However, little is known about the architecture of the proposed multicomplex assemblies. Here, we report the electron microscopic characterization of the two respiratory chain supercomplexes I 1 III 2 and I 1 III 2 IV 1 in bovine hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
192
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 253 publications
(209 citation statements)
references
References 35 publications
17
192
0
Order By: Relevance
“…Furthermore, the decrease in complex IV activity was more marked than for complex I activity. The exact reasons for this difference are not presently known, but the interdependence in activity of the respiratory complexes has been reported previously (33). This phenomenon establishes that complex I influences the behavior of other respiratory complexes typically complex III and/or complex IV.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, the decrease in complex IV activity was more marked than for complex I activity. The exact reasons for this difference are not presently known, but the interdependence in activity of the respiratory complexes has been reported previously (33). This phenomenon establishes that complex I influences the behavior of other respiratory complexes typically complex III and/or complex IV.…”
Section: Discussionmentioning
confidence: 88%
“…Schafer et al (10) showed that NADH: ubiquinone reductase was more active in supercomplex I:III 2 :IV than in supercomplex I:III 2 . This is the same step of electron transfer that is measured in our complex I assay.…”
Section: Table 2 Mrc Proteins Identified By Mass Spectrometry In Eachmentioning
confidence: 99%
“…[50] Oxygen plays key roles in the process of electron transfer in the respiratory chain. [51] Therefore, much effort has been focused recently on gas responsive nanochannels. Inspired by stomatal closure in response to CO 2 during photo synthesis, our group first reported CO 2 induced ionic current rectification in gas-liquid-solid three phase interactions based on conical PET nanochannels (Figure 4c i), but the highest rec tification ratio was only 4.60.…”
Section: Functional Modification Of Smart Bioinspired Nanochannelsmentioning
confidence: 99%